'Our relationship is different': exploring mothers' early experiences of bonding to their twins. (20th October 2021) - Gowling, Sarah A.; McKenzie-McHarg, Kirstie; Gordon, Carolyn; Harrison, Lesley K.
ABSTRACT: Objective : The aim of this research was to explore mothers' lived experience of early bonding with their twins. Background : Research has suggested that the process of bonding with twins may differ from that of bonding with singletons. However, there is limited research exploring this experience from the mother's perspective. Method : An IPA study involved six participants in semi-structured interviews. Results : Two superordinate themes emerged; 'Twin guilt and shame' and 'I missed out … they miss out'. Results suggested the experience of bonding with two infants simultaneously generated guilt for the mothers, who at points felt that they and their infants had missed out and had had to adapt. Conclusion : The experience of bonding with twins can be complex and take longer than anticipated, with mothers reporting the experience as being different from their expectations. Having a greater understanding and information about the complexities of bonding with twins would be beneficial for both mothers and professionals working with them.